Role of middle managers in strategic renewal. (16th May 2019) - Anas, Eka Pria; Afiff, Adi Zakaria; Prijadi, Ruslan
The present study discusses the development of strategic renewal through the role of middle managers who pay proper attention to changes in their respective business environments. The following three approaches are used in this study: strategic renewal, the attention-based view and the strategic role of middle managers and uses the state-owned enterprise infrastructure in Indonesia to illustrate that middle managers can influence the course of a firm's strategy. Middle managers at a particular position are more likely to change their firm-level strategies. Middle managers exert their influence by directing the attention of the top management to strategic opportunities. Such an effort is possible if middle managers pay attention to the changes in the firm's environment, which requires support from several organisational factors as well. However, such a middle manager role is more effective when it is played by managers who are knowledgeable and experienced.